Oncologists' views on ototoxicity monitoring in head and neck cancer patients: A South Indian qualitative study. - Varsha Shankar; Jayashree Seethapathy; Satish Srinivas; Raghu Nandhan; Prasanna Kumar Saravanam (PLoS ONE)
Aim The perspectives and practices of healthcare professionals regarding ototoxicity in individuals with head and neck cancers are important for the implementation of ototoxicity monitoring. The current study aims to explore the oncologist's awareness and perspectives of ototoxicity and ototoxicity monitoring for individuals with head and neck cancer in a South-Indian district, using qualitative semi-structured interviews. Method The COnsolidated criteria for REporting Qualitative research (COREQ) Checklist was used to guide the method of the current qualitative study. A conceptual framework was developed for the formulation of the interview guides. Three medical oncologists and six radiation oncologists from cancer care centres participated in the study. The interviews were audio recorded and transcribed verbatim. Thematic analysis was carried out using a hybrid inductive-deductive approach to present the findings under the respective overarching themes. Results All oncologists are aware of the ototoxic effects caused by radiation therapy and chemoradiotherapy. It was consistently reported that the severity of the hearing loss was not substantial enough to warrant significant concern. Ototoxicity is not emphasized during the counseling process. All participants reported having awareness and knowledge of ototoxicity monitoring programs and understood their importance. However, none of them reported the implementation of an ototoxicity monitoring program in their facility. Discussion It is imperative to enhance the knowledge and understanding of the ototoxic nature of cancer treatment modalities among oncologists. It is crucial to raise awareness regarding the significance of ototoxicity monitoring programs among all physicians involved in the treatment of patients with cancer for maximum impact. The barriers to implementing ototoxicity monitoring programs in high- and low-income countries are similar. The models implemented in high-income countries can be adapted for use in low-middle income countries with suitable restructuring. Conclusion The current study provides valuable insights into the status of ototoxicity monitoring in the South-Indian context. The findings align with the key components of the health belief model, including perceived susceptibility, perceived barriers, and cues to action. Involving oncologists in the planning phase of the ototoxicity monitoring programs can help tailor future research questions and solutions to improve quality of life, foster collaboration among healthcare professionals, and produce actionable outcomes that may influence policy on ototoxicity monitoring.